2016
DOI: 10.1108/hff-01-2015-0039
|View full text |Cite
|
Sign up to set email alerts
|

Steady state and transient analysis of compact plate-fin heat exchanger fins for generation of design data using CFD

Abstract: Purpose -The purpose of this paper is to carry out numerical modeling of single-blow transient analysis using FLUENT porous media model for estimation of heat transfer and pressure drop characteristics of offset and wavy fins. Design/methodology/approach -A computational fluid dynamics program FLUENT has been used to predict the design data in terms of j and f factors for plate-fin heat exchanger wavy and offset strip fins, which are widely used in aerospace applications. Findings -The suitable design data in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…Finally, the f and j values are generated using CFD technique for different types of offset strip fins and wavy fins. The complete results can be seen in earlier papers (Ranganayakulu et al , 2008; Sheik Ismail et al , 2009; Chennu and Paturu, 2011; Chennu, 2016; Rao et al , 2013, 2016, 2015; Ramana Murthy et al , 2015; Muppala et al , 2015). However, the correlations generated using CFD are listed below for various types of fins in Table II for ready reference.…”
Section: Cfd Analysissupporting
confidence: 57%
“…Finally, the f and j values are generated using CFD technique for different types of offset strip fins and wavy fins. The complete results can be seen in earlier papers (Ranganayakulu et al , 2008; Sheik Ismail et al , 2009; Chennu and Paturu, 2011; Chennu, 2016; Rao et al , 2013, 2016, 2015; Ramana Murthy et al , 2015; Muppala et al , 2015). However, the correlations generated using CFD are listed below for various types of fins in Table II for ready reference.…”
Section: Cfd Analysissupporting
confidence: 57%
“…Geometrical modification (wavy walls) combined with the use of nanofluid as the working media is one efficient method of passive heat transfer enhancement used satisfactorily for thermal systems such as solar collectors, heat exchangers and heat sinks. (Hatami and Jing, 2017;Priyam and Chand, 2016;Cheng et al, 2009;Tsai et al, 1999;Chennu, 2016;Comini et al, 2002Comini et al, , 2003. Rush et al (1999) through their experimental work found that the augmentation of heat transport takes place even for a laminar flow regime in a wavy channel due to the enhanced macroscopic mixing.…”
Section: Introductionmentioning
confidence: 99%
“…They are important in most cases for the narrow ranges of Reynolds and Prandtl number variations as conducting extensive experimental research is very laborious and expensive. Computational fluid dynamic (CFD) simulations are an alternative way of generating the relationships for the Nusselt number as a function of Reynolds and Prandtl numbers (Chennu, 2016; Khoshvaght-Aliabadi et al ., 2014). Chennu (2016) simulated a single-blow test to find correlations for the Colburn and friction factors for plate-fin heat exchanger with wavy and offset strip fins.…”
Section: Introductionmentioning
confidence: 99%